أساليب التفكير السائدة لدى الطلبة المتفوقين عقلياً في ضوء معدلاتهم التحصيلية والجنس - زحلوق, مها; بدور, لينا صالح (Latakia University Journal - Arts and Humanities Sciences Series, 2013)
سعى البحث الحالي للكشف عن أساليب التفكير السائدة لدى الطلبة المتفوقين عقلياً في ضوء معدلاتهم التحصيلية والجنس. وقد تم اختيار عينة البحث بشكل قصدي, وهي تتألف من (60) طالباً وطالبة من طلبة الصف الثاني الثانوي في مدرسة "ثانوية المتفوقين", واتبع البحث المنهج الوصفي التحليلي، واستخدم البحث قائمة أساليب التفكير لستيرنبرج وواجنر, ترجمة السيد أبو هاشم. وأظهرت نتائج البحث أن أكثر أساليب التفكير شيوعاً لدى الطلبة المتفوقين عقلياً أسلوب التفكير التشريعي، ثم أسلوب التفكير الهرمي والمتحرر، بينما كانت أقل الأساليب شيوعاً أسلوب التفكير المحافظ والعالمي والتنفيذي, كما أظهرت النتائج وجود علاقة ضعيفة جداً بين درجات الطلبة على أساليب التفكير( التشريعي والتنفيذي والعالمي والمحلي والمتحرر والمحافظ والملكي والفوضوي) وبين معدلهم التحصيلي، في حين وجدت علاقة ضعيفة مع الأسلوبين القضائي والأقلي، وعلاقة معتدلة مع كل من التفكير الهرمي والخارجي، وعلاقة سالبة مع التفكير الداخلي. كما تبين وجود فروق ذات دلالة إحصائية بين الطلبة المتفوقين عقلياً الذكور وبين الطلبة المتفوقين عقلياً الإناث من حيث أساليب التفكير في كل من أساليب التفكير الآتية (التفكير العالمي والمحافظ والهرمي والملكي والداخلي والخارجي) وذلك لصالح الذكور في أسلوب التفكير الداخلي، ولصالح الإناث في كل من أسلوب التفكير العالمي والمحافظ والهرمي والملكي والخارجي. The study seeks to identify the prevailing methods of thinking among the mentally talented students in the light of their achievement rates and gender. The sample of the research was chosen intentionally. It consists of second secondary grade students from "Top Students Secondary School". The study used the analytic, descriptive method, as well as the Sternberg & Wagner's list of methods of thinking, which was translated by Mr. Abu Hashem. The study showed that the most common methods of thinking for mentally talented students were legislative thinking, and liberal hierarchical thinking. The least common, on the other hand, were conservative thinking, global thinking and executive thinking. The study showed that the relationship between students' scores on certain thinking methods and their achievement rates was very weak. These methods are: legislative, executive, global, local, liberal, conservative, monarchic and anarchic. It was also found out that there was a weak relationship between students' scores on some other thinking methods and their achievement rates. These methods are: judicial methods and minority method. There is a moderate relationship regarding the hierarchical and external thinking. As the study showed that there was a statistically significant difference between the mentally talented male students and students excelling mentally in the following methods of thinking: global, conservative, hierarchical, monarchic, internal and external. This was in favor of males regarding internal thinking, and in favor of females regarding global, conservative, monarchic, hierarchical and external thinking.